Karakteristik Klinis Pasien Retinopati Diabetik di RSUD Dr. H. Chasan Boesoirie Ternate - Hamzah, Marwa R.D.W; Wardana, Ganesa; Nugroho, Aryandhito W. (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Background: By definition: Diabetic retinopathy (RD) is one of the microvascular complications of diabetes mellitus (DM) in DM patients that has been going on for a long time so that it can cause blindness. RD is sometimes asymptomatic so there is often a delay in diagnosing. This should be watched out for immediately because the increasing number of blindness can cause a decrease in the productivity of sufferers and affect the quality of life of patients and cause a social burden on society. Objective: To find out the clinical characteristic of DR patients at RSUD Dr. H. Chasan Boesoirie Ternate. Methods: The type of research is a descriptive observational study with a cross-sectional approach with a total sampling technique of 19 patients and using data from medical records period January 2020-January 2023 according to the inclusion criteria and used univariate analysis. Results: Characteristic of diabetic retinopathy patients 60% aged 45-65 years, 60% female, 60% work, 40% college graduates, 70% no history of hypertension, and 60% severe visual impairment or blindness (<3/60). The majority of diabetic retinopathy are aged 45-65 years, female, work, college graduates, no history of hypertension and severe visual impairment or blindness (<3/60).